Arab Spatial Development and Food Security Atlas - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
The Arab Spatial Development and Food Security Atlas is a “start-up” initiative of the International Food Policy Research Institute (IFPRI) that is supported by the International Fund of Agricultural Development (IFAD) and the Policies, Markets, and Institutions (PIM) Program of the Consultative Group of International Agricultural Research Centers (CGIAR). The main objective of Arab Spatial is to improve access to quality data and to support decision and policy making for a food-secure Arab world, covering the 22 member countries of the Arab League of Nations from Mauritania and Morocco in the West to Iraq and Oman in the East. Among the special features of Arab Spatial is the focus on the linkages between food security and development and the combination of indicators at the national, subnational, and pixel levels, often available as time-series data.